What Should a Lower Primary School Teacher Be Like from a School Management's Point of View? - Skutil, Martin; Maněnová, Maněnová, Martina (Revija za elementarno izobraževanje, 2009)
Current society requires a high level of performance from teachers. There are some ideas about ideal teachers concerning either their professional and didactic skills or personality. This article presents some partial results of our research in which we wanted to find out the ideas that school leaders have about primary school teachers. This project was based on empirical research that was done qualitatively and quantitatively and is general ly divided into two phases. Combining both approaches seemed to be a convenient research strategy with the first phase, being a quality-based interview followed by a quantity-based study. The results show that school leaders mostly expect their teachers to have the following personal characteristics: emotional stability, resistance to stress, tolerance, openness, a sense of humor, ability to be self-critical, compassion as well as being skilled in didactics. The most important professional competence school leaders chose was psycho-didactical competence. Managerial and normative competences were set back.